Mucinous cystic neoplasm diagnosed by EUS-guided microforceps biopsy - Orr, Jordan; Lockwood, Robert; Salaria, Safia; Gamboa, Anthony; Yachimski, Patrick (Endoscopy International Open, 2018)
Background and study aims Mucinous cystic neoplasms (MCNs) of the pancreas have malignant potential. Current methods for diagnosing MCNs are inadequate. The aim of this case series is to present a novel method for establishing the diagnosis of MCNs. Clinical information from three patients seen at our institution was collected for a case series presentation. Patients were selected retrospectively based on diagnostic results. Three patients were diagnosed with MCNs based on histopathology obtained via microforceps biopsy. Evolving tissue acquisition techniques, such as microforceps intracystic biopsy, have improved the diagnostic yield of endoscopic ultrasound (EUS).